Integrated Design of Solar Energy Utilization and Building Based on PLC. Issue 1 (October 2020) - Zhou, Li; Chen, Bo; Liu, Yang
Abstract: At present, fossil energy consumption still occupies a dominant position in China's energy consumption structure, and problems such as low energy consumption efficiency, high degree of carbonization and large environmental pollution persist for a long time. Under the background of advocating environmental protection and energy saving, the combination of solar energy and building is the inevitable trend of building energy saving development, and the integrated design of solar energy and building has become a concern of the architectural circles. With the deepening of people's understanding of environmental problems and the further deterioration of energy problems, more and more buildings begin to use clean and energy-saving solar energy devices. At present, the construction and development of urban residential buildings in China are mainly multi-storey and high-rise buildings. Therefore, higher requirements are put forward for the application form and scale of solar water heating system in residential buildings. In this paper, according to the current situation of solar energy utilization in buildings in China, based on PLC (programmable logic controller), the paper puts forward some suggestions to promote the integrated design of solar energy buildings.